1996
DOI: 10.1093/hmg/5.8.1155
|View full text |Cite
|
Sign up to set email alerts
|

Mouse/human sequence divergence in a region with a paternal-specific methylation imprint at the human H19 locus

Abstract: We have identified a region with characteristics of a paternal-specific methylation imprint at the human H19 locus. This region, extending from -2.0 kb upstream to the start of transcription, is heavily methylated in sperm and on the paternal allele in somatic cells. This methylation was preserved during pre-implantation. Structural analysis revealed the presence of CpG islands and a large direct repeat with a 400 bp sequence reiterated several times, but no significant sequence homology to the corresponding r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(62 citation statements)
references
References 23 publications
3
59
0
Order By: Relevance
“…3). This was consistent with previous analyses of H19 methylation in human somatic cells (Zhang et al 1993;Jinno et al 1996). These results indicated that the appropriate imprinting status of human H19 was maintained in these mouse somatic cell hybrids.…”
Section: Maintenance Of the Imprinting Status Of Human H19 In Mouse Ssupporting
confidence: 93%
“…3). This was consistent with previous analyses of H19 methylation in human somatic cells (Zhang et al 1993;Jinno et al 1996). These results indicated that the appropriate imprinting status of human H19 was maintained in these mouse somatic cell hybrids.…”
Section: Maintenance Of the Imprinting Status Of Human H19 In Mouse Ssupporting
confidence: 93%
“…1) and is normally maternally methylated (IGF2 DMR; ref. 28), whereas another is located upstream of H19 and is paternally methylated (29). The latter region harbors sequences known to bind to the zinc finger protein CTCF in a methylation-sensitive manner (18,30).…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether there is abnormal methylation in the H19-DMR of HNSCC patients, we modified a protocol based on methylation-sensitive restriction enzyme PCR and posterior RFLP analysis, which permits allele differentiation (33). Using an AvaI RFLP, 91/95 cases were genotyped and 22 heterozygous informative cases were detected.…”
Section: Genomic Polymorphisms For Screening Of Informative Cases Andmentioning
confidence: 99%